Rite and Performance : Tools for Transmission of Cultural Memory - Borjan, Etami (2009)
The paper analyzes Italian ethnographic documentaries on possession, exorcist rites and ritual dances shot in South Italian rural communities. The aim of the paper is to analyze the ways in which these “social dramas”, as Victor Turner calls them, are being performed and presented to the community. All types of exorcist rites include public performance similar to a mise en scène where the participants not only act but are conscious of what they’re doing.
Projekt MZOS
ENG